Roadmap for UN 2030 Education Agenda for Learners with Special Educational Needs of Department of Education, Pangasinan Division II, Philippines - Donato Balderas; Marites Tabuga; Jupiter Lopez Petilla (Department of Special Education, 2018)
The UN 2030 Education Agenda is a global platform directed towards creating opportunities for learners with special educational needs (LSENs) for their holistic development and eventual mainstreaming in the society. The schools being the catalysts of societal transformation are focal points for the provision of instruction and intervention that emphasize inclusion, equity and gender equality among learners. Policies, programs, activities as well teachers’ training and orientation must be crafted to address the proper mainstreaming and placement of LSENs that will prepare them for self-independence and enhancement of their skills while ensuring that incidents of gender bias and bullying is eliminated, thus creating a wholesome learning environment. The objectives of this paper are mainly focused on the following areas; emphasis on the level of awareness of the goals of UN 2030 Education Agenda; assess the level of effectiveness of initiatives and activities for implementation; point out the severity of the problems that hinder implementation. A plan of action reflected as the roadmap in order to attain the UN 2030 Education Agenda was conceptualized. Descriptive-analytical method of research was employed with survey-questionnaire as its data-gathering instrument. Respondents were teachers and stakeholders of the eleven (11) special education centers of DepEd Division of Pangasinan II. From the data gathered, it was concluded that respondents have a very high awareness of the goals of UN 2030 education agenda, the initiatives and activities to be undertaken were perceived very much effective while the problems were moderately severe. The findings indicated that principals should keep track of the activities being implemented to ensure alignment with the set of goals, stakeholders must work collaboratively to intensify the implementation of the activities and that applicable solution must be thought of to minimize the problems encountered. Hence, principals in unison with the teachers and stakeholders must religiously implement the plan of action to ensure achievement of the goals on providing inclusive, equitable and gender equality education for learners with special educational needs of DepEd, Pangasinan Division II, Philippines